REBRANDING MADRASAH THROUGH EDUCATIVE DA'WAH COMMUNICATION: CHALLENGING SECULAR EDUCATIONAL HEGEMONY IN ISLAMIC EDUCATION DISCOURSE - Noerzanah, Firda; Azzahra, Fatimatul Mardiah; Az`Zahra, Nurul Afifah; Ridwan, Syahrul; Hidayatullah, M. Baihaki (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2026)
This study aims to analyze the role of educational da'wah communication in developing the image of madrasas from an Islamic Religious Education perspective. The study focuses on how communication based on Islamic values can shape public perception and strengthen the institutional identity of madrasas. This study uses a qualitative approach with library research, examining various scientific literature sources, including books, journal articles, and other relevant documents related to da'wah communication, Islamic education, and the image management of educational institutions. The results show that educational da'wah communication plays a strategic role as a medium for internalizing Islamic values, such as honesty (ṣidq), trustworthiness (amanah), transparency (tablīgh), and intelligence (faṭānah), which contribute significantly to building a positive and sustainable madrasah image. Madrasah image is shaped not only by academic quality but also by the consistency between idealized values and actual practices in institutional life. Furthermore, an effective communication strategy requires systematic planning, appropriate media selection, and the packaging of educational and valuable messages. The use of digital media is also a crucial factor in expanding communication reach, while still maintaining ethical communication practices from an Islamic perspective. This study concludes that educational da'wah communication is a relevant and effective approach to developing the image of madrasas, while also serving as an instrument of social transformation in shaping a religious and character-based society. The implications of this research emphasize the importance of integrating Islamic values, communication strategies, and institutional practices in strengthening the existence of madrasas amidst the dynamics of modern education.